Central Banking and Money Market Changes - Minsky, Hyman P. (Quarterly Journal of Economics, 1957)
I. Introduction, 171. — II. Two recent institutional changes, 173; the federal funds market, 173; the financing of government bond houses: sale and repurchase agreements with nonfinancial corporations, 176. — III. Implications of these changes for monetary policy, 181. — IV. Implications of the expectation that institutions will change, 185.